2011
DOI: 10.3892/ijo.2011.1183
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of CXCR4, DNMT3A, DNMT3B and DNMT1 gene expression in primary advanced uterine cervical carcinoma

Abstract: Abstract. The development of cervical cancer requires genetic and epigenetic factors which result in the persistence of a malignant phenotype. Cervical cancer exhibits also some unique differences from other solid tumors. Normal cervical stratified epithelia have characteristics of hypoxic tissue with over-expression of HIF-1 (hypoxia-inducible factor-1) transcription factor, which targets the transcription of over 70 genes involved in many aspects of cancer biology. One of the genes, which could be induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
(65 reference statements)
2
13
1
1
Order By: Relevance
“…Similar negative correlations between CXCR4 expression and promoter methylation have been shown in pancreatic cancer [19] and melanoma cells [34]. Our result is contradictory to the previous report of Łuczak et al [18] that CXCR4 promoter is not methylated in CC biopsy samples. The dietary intake is known to influence the pattern of global and targeted methylation of genome (reviewed by Alshatwi and Shafi) [35].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Similar negative correlations between CXCR4 expression and promoter methylation have been shown in pancreatic cancer [19] and melanoma cells [34]. Our result is contradictory to the previous report of Łuczak et al [18] that CXCR4 promoter is not methylated in CC biopsy samples. The dietary intake is known to influence the pattern of global and targeted methylation of genome (reviewed by Alshatwi and Shafi) [35].…”
Section: Discussioncontrasting
confidence: 81%
“…Exploring the autocrine and paracrine signaling, Tsujikawa et al [16] have demonstrated that chemokine CCL22 produced by cancer cells themselves (autocrine) or by other types of cells, for example, macrophage (paracrine), increased the cell motility of CCR4 + head and neck squamous cell carcinoma cells in vitro . CXCR4 has been shown to be upregulated in many of the solid tumors including cervical cancer (CC) [17, 18]. Also, downregulation of CXCR4 has been demonstrated in pancreatic cancer cell [19] and CD34 + cells [20] of patients with primary myelofibrosis due to promoter hypermethylation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the negative correlation between expression of DNMT1 and DNMT3a versus BTG2 in MIBC ( Table 1) further indicates a role for BTG2 expression in muscle invasion of bladder cancer, and its regulation by DNMTs. It is known that expression of tumor suppressor genes in cancer tissues and cells is regulated by DNA methylation of the promoter region by DNMT1, DNMT3a or DNMT3b [45][46][47][48]. Due to significant individual human variations, absolute values of DNMTs and BTG2 expression in human, normalized against GAPDH expression, did not reveal any significant correlations between their expression.…”
Section: Discussionmentioning
confidence: 95%
“…A study showed that DNMT1 and DNMT3A mRNA levels were higher in human kidney tumor tissues than in adjacent normal tissues (Robertson et al, 1999), and the expression of DNMT1 and DNMT3A proteins was higher in RCC tumors than in nontumor tissues (Li et al, 2014b). High DNMT1 and DNMT3A expression also was found in poorly differentiated retinoblastoma (Qu et al, 2010) and advanced uterine cervical carcinoma (Luczak et al, 2012). Cao et al reported that DNMT1 and DNMT3A expression was higher in human gastric carcinoma tissues than in adjacent normal gastric epithelial tissues, and DNMT3A expression was significantly related to poor survival (Cao et al, 2014).…”
Section: Discussionmentioning
confidence: 97%